Simulação Monte Carlo de cenários de radiologia intervencionista pediátrica no código MCNPX - Cavalcante, Fernanda Rocha (2017)
Interventional radiology consists of minimally invasive procedures guided by real-time X-ray imaging of a region of the patient to be diagnosed or treated. Since it is a practice that uses ionizing radiation, performing these procedures should follow the three basic principles of radioprotection, which are justification, optimization (medical exposure), and dose limitation (occupational exposure). Interventional procedures in children with congenital heart defects are justified by substituting other high-risk procedures. However, as these procedures are responsible for high doses in the patient and individuals occupationally exposed (IOE), it is important to evaluate the medical exposures of pediatric individuals due to a greater susceptibility to radiation damage in these individuals who present a rapid metabolism and closer proximity of the organs. In addition, the longer life expectancy in children allows more time for any harmful effects of radiation, such as cancer, to manifest. Because direct dose measurement within the human body is difficult or impractical, the Monte Carlo simulation of radiation transport is a useful tool in estimating dosimetric protection quantities (H T and E) in anthropomorphic phantoms representing the anatomy of the human body. In addition, it is possible to calculate conversion coefficients that relate protection quantities with measurable quantities, such as the kerma-area product (PKA). In this work, we modelled paediatric interventional cardiology scenarios using the MCNPX code and a pair of adult and paediatric hybrid anthropomorphic phantoms (newborn, 1 year and 5 year) to evaluate medical and occupational exposures. The results obtained in this work show conversion coefficients H T /PKA and E/PKA of 5 to 16 times higher than the values obtained in the literature for interventional procedures performed in adult patients. In addition, we estimate the influence of personal protective equipment (lead apron, thyroid shield and lead glasses) on occupational exposures, which contribute to reduction of H T doses in the physician up to 98% (gonads and thyroid), when used.